(untitled) (Papeles, 2024)
In recent years, due to the massive mobilizations of the feminist movement, the gender perspective has entered with greater force in Argentine university institutions. Within this framework, among the issues that have been promoted in their academic agendas is the incorporation of the gender perspective in scientific research. This responds to the long history of gender spaces at the national level. This paper proposes to take up this path again, situating ourselves locally. The present research, framed in a longer work, aims to describe the gender plans and actions in research designed and implemented by the Universidad Nacional del Litoral (UNL). The methodological design used was qualitative. The gender plans carried out by the UNL were systematized, a document analysis of them was carried out and four in-depth interviews conducted in 2018 were used as a secondary source. As a result of the work, the relevance of the UNL in the field at the national level and its intertwining with the broader socio-political context is evident.